Peran Strategis Media Pembelajaran PAI Berbasis Digital di SMA - Yogi Setiawan; Fani Nurjanah; Erik Wilgian Ramadhan; Fiqra Muhamad Nazib (Advances In Education Journal, 2024)
The role of digital-based learning has a very strategic role, including increasing students’ interest in learning and developing digital skills. To strive for quality education, teachers often find difficult to provide lesson material. Technology-based learning will makes it easier for students to understand the material taught by the teacher. This research aims to analyze how digital-based PAI learning media can be utilized optimally in high school, so that it can improve the learning process and student learning outcomes. This research method uses a systematic literature review (SLR) which aims to identify, evaluate and synthesize existing research. The literature review was carried out in stage 1) formulating research question, 2) searching for literary materials, 3) selecting literature, 4) analyzing and interpreting data, 5) drafting articles, and 6) disseminating results.